Membrane Cascade Fractionation of Tomato Leaf Extracts—Towards Bio-Based Crop Protection - Emmanouil H. Papaioannou; Fabio Bazzarelli; Rosalinda Mazzei; Vasileios Giannakopoulos; Michael R. Roberts; Lidietta Giorno (Membranes, 2023)
Promising initial results from the use of membrane-fractionated extracts of tomato leaf as crop protection agents have recently been reported. This paper provides additional evidence from larger scale experiments that identify an efficient pipeline for the separation of tomato leaf extracts to generate a fraction with significant defence elicitor activity. A UF tubular membrane 150 kDa, with an internal diameter of 5 mm, proved appropriate for initial extract clarification, whereas afterwards a UF 10 kDa and three NF membranes (200–800 Da) in sequence were evaluated for the subsequent fractionation of this tomato extract. The compositions of sugars, proteins and total biophenols were changed in these fractions with respect to the initial extract. The initial extract ratio of sugars: proteins: biophenols was 1:0.047:0.052, whereas for the retentate of the 800 Da NF membrane, which has the higher crop protection activity, this ratio was 1:0.06:0.1. In this regard, it appears that the main crop protection effect in this fraction was due to the sugars isolated. It was found that with the appropriate membrane cascade selection (UF 150 kDa, UF 10 kDa and NF 800 Da) it was possible to produce (easily and without the need of additional chemicals) a fraction that has significant activity as an elicitor of disease resistance in tomato, whereas the remaining fractions could be used for other purposes in a biorefinery. This is very promising for the wider application of the proposed approach for the relatively easy formulation of bio-based aqueous streams with bio-pesticide activities.